Two Sides of the Same Coin: A Combination of Archaeometallurgy and Environmental Archaeology to Re-Examine the Hypothesis of Yunnan as the Source of Highly Radiogenic Lead in Early Dynastic China - Liu, Ruiliang; Pollard, A. Mark; Lv, Feiya; Huan, Limin; Zhang, Shanjia; Ma, Minmin (Frontiers in Earth Science, 2021)
Bronze Age Shang China is characterized by its large-scale production system and distinctive ritual world. Both are vividly materialized by a large number of bronze ritual vessels with added lead. Whilst a remarkable amount of research effort has been channeled into the trace elemental and lead isotopic analysis of these ritual vessels, and successfully revealed some important fingerprints such as highly radiogenic lead (HRL), there is as yet no consensus on the metal source(s) which supplied the entire bronze production during the Shang period. In addition to the traditional method to look for matching and mismatching between ores and objects, we propose that environmental archaeological studies can provide crucial clues to address some long-standing questions in archaeometallurgy. In the first part of the paper, we attempt to illustrate the potential and complexity of combining these two subjects together. The second part of the paper offers a case study by reviewing the debate on Yunnan as the source of HRL. Synthesis of various lines of evidence published by most recent studies on environmental archaeology, archaeometallurgy, field reports and radiocarbon dating suggests that this hypothesis appears much less likely than previously suspected.